DISCUSSION AS THE MEANS OF THE ENGLISH LANGUAGE COMMUNICATIVE COMPETENCE FORMATION - S. Zahorulko; M. Kryvych (Borys Grinchenko Kyiv Metropolitan University, 2017)
The paper presents the analysis of the contemporary approaches to determine stages that are essential for teaching discussion and argues the necessity of distinguishing stages in the discussion teaching grounded on the problem-based situation; constitutes requirements for the discussion exercises which develop students' mental activity, appeal to various types of the memory, encourage students' unprompted speaking; proves the idea of considering discussion as the one of most significant means to develop English language communicative competence; presents an original set of assignments developed on the authentic video and reading materials to teach discussion grounded on the problem-based situation.